Death benefit - Cook, Robin, 1940- (New York : G.P. Putnam's Sons, 2011)
Launching a private investigation when their mentor dies under suspicious circumstances, medical students Pia Grazdani and George Wilson uncover a sinister operation through which private life insurance policies are being manipulated to allow investors to benefit from the deaths of others.
Keywords: Medical research personnel -- Fiction; Life insurance -- Fiction; Medical novels; Mystery fiction